Clinical Risk Factors for Head Impact During Falls in Older Adults: A Prospective Cohort Study in Long-Term Care. Issue 3 (May 2017) - Yang, Yijian; Mackey, Dawn C.; Liu-Ambrose, Teresa; Leung, Pet-Ming; Feldman, Fabio; Robinovitch, Stephen N.
Abstract : Objective: To examine risk factors associated with head impact during falls in older adults in long-term care (LTC). Setting: Two LTC facilities in British Columbia, Canada. Participants: 160 LTC residents. Design: Prospective cohort study. Main Measures: Between 2007 and 2014, we video captured 520 falls experienced by participants. Each fall video was analyzed to determine whether impact occurred to the head. Using generalized estimating equation models, we examined how head impact was associated with other fall characteristics and health status prior to the fall. Results: Head impact occurred in 33% of falls. Individuals with mild cognitive impairment were at higher risk for head impact (odds ratio = 2.8; 95% confidence interval, 1.5-5.0) than those with more severe cognitive impairment. Impaired vision was associated with 2.0-fold (1.3-3.0) higher odds of head impact. Women were 2.2 times (1.4-3.3) more likely than men to impact their head during a fall. Conclusion: Head impact is common during falls in LTC, with less cognitively impaired, female residents who suffered from visual impairment, being most likely to impact their head. Future research should focus on improving our ability to detect neural consequences of head impact and evaluating the effect of interventions for reducing the risk for fall-related head injuries in LTC. Abstract : Supplemental Digital Content is Available in the Text.